Políticas de formação de professores para a educação profissional e tecnológica: cenários contemporâneos - Costa, Maria Adélia da (2012)
The present investigation had as subject of study the teacher education policies for Professional and Technological Education (EPT in Portuguese). Reflecting on teacher education policies for EPT, in a model of society ruled by the capitalist and neoliberal logic, is a challenge that arises in our daily lives because we are actors and authors who make and remake, directly or indirectly, Brazilian education history. The thesis that guided this research was the lack of policies on teacher education for EPT. In this sense, the documentary analysis and literature surveys enabled us to realize that, throughout their history, policies in this area have not set yet as State policy, but rather as government programs that aim to facilitate and regulate the access for professionals (not teachers) to the classrooms of technological education. Regarding these policies, there are the relations among education, work and society. In this context, we discuss and confront the teacher education policies for EPT from the 1990s until today. This starting point, the 1990s, is due to the fact that it was a decade of expansion of college education in Brazil. However, our emphasis will start in 2007, with the implementation of Federal Institutes for Education, Science and Technology (IFETs in Portuguese), which, since then, are obligated to offer teaching degree courses, mission previously delegated to universities. In this context, we sought to understand the meanings and the materialization of the teaching profession in a context where a teaching degree is not a necessary requirement for professional practice, especially in institutions that have no previous experience in providing these kids of courses. The results showed the following situations: i) the materialization of lightened, discontinuous and fragmented teacher education courses programs for EPT; ii) the extraordinary expansion of the Federal Network for Education, Science and Technology has required a greater number of teachers for this level of education; iii ) we identified that the documents of PDIs and PPPs from the IFETs investigated follow MEC / SETEC policies iv) we noticed that some IFETs do not include professional education in basic education, therefore, they are dedicated to educate teachers for basic education, considering only elementary and high school; v) we identified a close link between the category of work and production models; vi) we found that, in New Developmental government of ex-President Lula, there was development of inclusive education policies, consolidated by the IFETs expansion, which, therefore, represented a considerable increase in jobs positions at all levels of professional education. However, we believe that Lula s government has left many conflict situations in order to reach its goal of social inclusion; vii) we perceived a lack of MEC's interest in discussing and regulating policies for teacher education for EPT and also in promulgating national guidelines for such education; and viii) we realized that the institutes themselves are organized in order to value teaching degrees so that they can ensure the requirement for this kind of degrees or special programs for teacher education, in order to practice teaching profession.